Bridging the Generation Gap: Communication Strategies at Golkar Sidoarjo DPD - Wardani, Anggraini Kusuma; Sufyanto, Sufyanto (Indonesian Journal of Cultural and Community Development, 2024)
Background: Effective communication in organizations is crucial for fostering collaboration, especially in diverse generational settings. Specific Background: This study investigates the communication dynamics at DPD Golkar Sidoarjo, using a qualitative approach to explore interactions among staff from different generations. Knowledge Gap: While previous research has addressed generational gaps in workplace performance, there is limited understanding of how communication strategies can effectively bridge these divides. Aims: The study aims to analyze vertical and horizontal communication, alongside openness and feedback, in addressing generational differences. Results: Findings reveal that adaptive communication strategies successfully manage these differences, enhancing inclusivity and productivity. Novelty: This research provides insights into tailored communication approaches that respect generational preferences. Implications: The study highlights the need for strategic communication frameworks in human resource management to facilitate effective interactions among diverse generational cohorts, improving organizational performance. Highlights : Adaptive Strategies: Effective communication tailored to generational preferences enhances collaboration. Team Dynamics: Horizontal communication fosters teamwork and idea-sharing among staff. Productivity Impact: Addressing generational gaps through communication improves overall organizational performance. Keywords: organizational communication, generational differences, qualitative study, DPD Golkar Sidoarjo, inclusivity